Prevalence of having a regular doctor, associated factors, and the effect on health services utilization: a population-based study in Southern Brazil - Mendoza-Sassi Raúl; Béria Jorge U. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
In order to assess the prevalence of having a regular doctor, associated factors, and the effects on health services utilization, a cross-sectional study was performed in Rio Grande, Brazil, from January to May 2000. A total of 1,260 individuals 15 years or over were interviewed. Adjusted prevalence ratios and 95% confidence intervals were calculated, using a Poisson regression model. Some 37% of the sample had a regular doctor. Adjusted analysis revealed a direct and linear association with income. Female gender, age, private health insurance coverage, and chronic health problems were also associated with the outcome. Having a regular physician was associated with a 51% increase in clinical breast examination and a 62% increase in cervical cancer screening during the previous year, as well as a 98% increase in prostate cancer screening in the previous year in men 40 years or over. The study concluded that the prevalence of having a regular doctor in Brazil is low and is directly associated with socioeconomic factors. Individuals with a regular physician tend to have better access to health services. The promotion of consultation with a regular doctor among the population may improve health care quality and health services access, particularly in the poorest groups.